Desain dan Konstitusionalitas Penerapan Pilkada Asimetris di Indonesia - Kusuma, Lalu Aria Nata (UI Scholars Hub, 2025)
The idea of implementing asymmetric regional elections (Pilkada) in Indonesia is not a new concept. However, to date, there has been no effort to provide a design for the implementation of Pilkada in an asymmetric manner, considering the specific needs of each region and its alignment with the 1945 Constitution. This article aims to implement Pilkada in an asymmetric manner by first mapping the asymmetry models of each region based on their specific needs. This research uses a doctrinal and socio-legal approach. The results of this research indicate a need to implement Pilkada asymmetrically in Indonesia. This urgency arises due to issues such as vote-buying, horizontal conflicts, electoral fraud, manipulation of results and processes, the lack of neutrality among State Civil Apparatus (ASN), and various other problems that characterize the implementation of Pilkada in multiple regions. The implementation of asymmetric Pilkada is carried out by first mapping the region's needs. There are four options for models of asymmetric Pilkada: political asymmetric Pilkada, special administrative asymmetric Pilkada, general administrative asymmetric Pilkada, and political-administrative asymmetric Pilkada. In the classification of these models of asymmetric Pilkada, the general administrative asymmetric Pilkada and political-administrative asymmetric Pilkada derive their asymmetry based on the Human Development Index (IPM) and the financial capacity of the region. Regarding the constitutionality of asymmetric Pilkada, there are three primary considerations: First, asymmetric Pilkada can strengthen the idea of a unitary state, given the consideration that the unitary state practiced in Indonesia involves aspects of asymmetric decentralization, of which asymmetric Pilkada is a derivative. Second, the democratic element of implementing Pilkada remains guaranteed, as the interpretation of democracy does not limit itself to the form of direct Pilkada alone. Third, the implementation of asymmetric Pilkada does not contradict the principle of